Mental Health in Cultural Contexts: Responses to Culturally Based Interventions - Aini, Siti Noor (Research Psychologie, Orientation et Conseil, 2024)
Mental health is a global issue, but responses to mental health interventions can vary significantly across different cultural contexts. Culturally based interventions, which consider the social, spiritual, and cultural values of specific communities, are increasingly recognized as vital to improving mental health outcomes. However, there is limited research on how these culturally tailored approaches impact mental health in diverse populations. This study aims to explore the effectiveness of culturally based mental health interventions and examine how cultural values and practices influence responses to these interventions in different communities. A mixed-methods approach was employed, involving both quantitative and qualitative data. Surveys and clinical assessments were conducted to measure mental health outcomes among participants in culturally tailored interventions across four different cultural contexts. Additionally, in-depth interviews were held with participants to understand their experiences and perceptions of the interventions. Data were analyzed using statistical analysis for quantitative data and thematic analysis for qualitative insights. The findings revealed that culturally based interventions led to significant improvements in mental health outcomes compared to standard interventions. Participants reported higher levels of engagement, satisfaction, and perceived relevance of the interventions to their cultural values. Differences in intervention outcomes were observed across cultural groups, highlighting the importance of tailoring approaches to specific cultural contexts. Culturally based interventions play a crucial role in improving mental health outcomes by aligning with the cultural values and practices of communities. These interventions should be integrated into mental health strategies to ensure more effective and inclusive care.